CRISTA BRADLEY, If These Places Could Talk: Snapshots of Saskatchewan - Sweeney, Shelley (Archivaria, 2021)
If These Places Could Talk: Snapshots of Saskatchewan. Crista Bradley, with artwork by Wendi Nordell. Regina: Your Nickel’s Worth Publishing, 2020. 48 pp. 978-1-988783-59-8